A role for FGFR1 in paediatric gliomas. (31st January 2018) - Egbivwie, Naomi; Warr, Tracy; Humphries, Matthew; Esteves, Filomena; Short, Susan; Cockle, Julia; Brüning-Richardson, Anke
Abstract: INTRODUCTION: Paediatric high-grade gliomas (pHGGs) are highly invasive tumours associated with extremely poor prognosis. There is urgent clinical need to develop novel therapeutic strategies that can target the process of tumour migration and invasion. Fibroblast growth factor receptors (FGFRs) are transmembrane receptor tyrosine kinases associated with glioma tumourigenesis that play a role in regulating cell migration and invasion. An increased frequency of FGFR1 mutations has recently been described in paediatric gliomas (Zhang et al. 2013). Here, the role of FGFR1 in paediatric gliomas was investigated. METHOD AND MATERIALS: FGFR1 levels (phosphorylated/unphosphorylated) and cellular localisation were determined by immunofluorescence in two pHGG cell lines (KNS42 and SF188) and five short-term cultures derived from pilocytic astrocytomas (grade 1). FGFR1 activity was stimulated by addition of FGF2. The activity of three FGFR1 inhibitors on cell migration after stimulation was assessed by live cell imaging and in a 3D spheroid invasion assay. FGFR1 levels in low and high-grade paediatric and adult tumour types were investigated in a commercial tissue microarray (TMA). RESULTS: FGFR1 was found to be expressed among all cell lines examined by immunofluorescence. Phosphorylated (activated) FGFR1 was elevated in some cell lines after stimulation with FGF2. Live cell imaging of inhibitor-treated cells and spheroid invasion assays suggest pro-migratory effects of FGFR1 inhibition in low-grade versus anti-migratory in high-grade tumours. High FGFR1 expression in astrocytomas from patients aged under 18 compared to the 18–60 age group (χ2 = 11.578, p = 0.0031) was determined in the TMA sample set. There was a significant association of high FGFR1 levels with grade 2 and 3 astrocytomas. DISCUSSION: We report the presence of FGFR1 among low and high-grade paediatric gliomas and a role in cell migration after stimulation with ligand. Treatment with FGFR1 inhibitors may elicit a different effect on cell migration depending on tumour grade.